Nurse-led interventions for diabetes education: a literature review - Mat Isa, Rif'atunnailah; Chong, Mei Chan; Lee, Wan Ling; Mohamed Iqbal, Tajunisah Begam; Jamaludin, Thandar Soe Sumaiyah; Saiful Suhardi, Mohd Iman (IIUM Press, 2023)
Background: The incidence of blindness is escalating to 439 billion patients by 2030. This study aims to review studies of health education related to diabetic retinopathy that have been implemented to inform nurse-led intervention to patients with type 2 diabetes mellitus (T2DM). Methods: A comprehensive search of the database was performed from October 2021 until March 2022. The databases include CINAHL, EMERALD insight, SAGE, Scopus, Web of Science and Science Direct. The Medical Subject Headings database was used to derive the following keywords: ‘T2DM' OR ‘Diabetes Mellitus type 2’, Diabetic Retinopathy’ OR ‘Diabetic eye’ OR ‘retinopathies') AND ‘education’, self-care’, ‘visual quality of life’, ‘mHealth’. All studies in English pertaining to the type of teaching and the effects of education on the visual quality of life among T2DM patients were included. Type 1 diabetes mellitus studies were excluded. Analysis of the themes arising from the results was performed. Results: The search yielded 868 articles, of which 27 met our criteria. The studies ranged from cross-sectional, controlled studies, quasi-experimental studies, and qualitative studies. Overall, there was three types of health education interventions: personalised, group-based, and technology-based. Conclusion: There is paucity in nurse-led health education about diabetic retinopathy in East Asia. It appears that conventional health education helpful, but the mobile application might be an option to provide better health education, with an emphasis on diabetic retinopathy components.